SOLUNUM GÜÇLÜĞÜ SORUNU İLE İZLENEN YENİDOĞAN BEBEKLERDE PLAZMA ENDOTELİN 1, PLATELET ACTİVATİNG FAKTÖR ASETİLHİDROLAZ TRANSFORMİNG GROWTH FAKTÖR BETA1 DÜZEYLERİ İLE AYRICI TANIDA KULLANILABİLİRLİKLERİ - BENZER, DERYA (Fırat Üniveristesi, 2006)
Prematür doğumlarda hastanede yatış süresinin uzamasının en önemli nedenisolunum sistemi ile ilgili sorunlardır. Respiratuar distres sendromu tip 1, respiratuardistres sendromu tip 2, mekonyum aspirasyonu solunum güçlüğünün en sıknedenlerinden olup, hastalığın erken tanımlanması ve zamanında başlanılan uyguntedavi yaşam kalitesini ve süresini uzatmada önemlidir.Bronş daralması ve damar daralmasından sorumlu tutulan endotelin-1'in birçok organ yetmezliğinde artmış düzeyleri kötü prognoz ile ilişkilidir. Transforminggrowth faktör beta ise enflamasyonu düzeltici ve doku onarımını arttırıcı etkigösterdiği halde, yüksek düzeyde birikmesi enflamasyonun uzamasına ve fibroziseneden olur. Bir diğer sitokin platelet aktivating faktör ise akciğerlerde vazoaktifetkiye neden olur ve bronş daralmasını uyarır. Platelet aktivating faktör asetilhidrolazise PAF'ı parçalayarak etkisiz hale getiren enzimdir.Bu çalışmada solunum güçlüğü ile getirilen yenidoğanların ayırıcı tanısında,izleminde ve prognozun belirlenmesinde serum endotelin-1, transforming growthfaktör beta-1 ve platelet aktiveting faktör asetilhidrolaz düzeylerinin bakılmasınınanlamlılığının değerlendirilmesi amaçlandı.Çalışmaya yenidoğan yoğun bakım ünitesine solunum güçlüğü nedeni ileyatırılan bebekler alındı. Bir yıl içerisinde içerisinde respiratuar distres tanısı alan 62,RDS tip 2 tanısı alan 24 hasta, mekonyum aspirasyonu tanısı alan 14 hasta olmaküzere 100 yenidoğan çalışma grubu oluşturuldu. Ayrıca herhangi bir yakınmasıolmayan 20 prematür ve matür bebekten kontrol grubu oluşturuldu. Endotelin-1,transforming growth faktör beta ve platelet aktiveting faktör asetilhidrolazın kontrolgrubundaki prematür ve matür bebeklerde farklılık göstermediği; endotelin 1 vetransforming growth faktör beta'nın en fazla mekonyum aspirasyonunda artmış1olmakla birlikte sırası ile RDS tip 1 ve RDS tip 2' de de artmış olduğu bulundu.Platelet aktiveting faktör asetilhidrolaz düzeyinde artış ise sadece mekonyumaspirasyonunda belirlendi. lk saatlerde bakılan endotelin-1'in prognozu belirlemededaha yararlı olduğu ve ilerleyen günlerde bakılan endotelin 1'in klinik iyileşmeyigöstermede daha anlamlı olduğu gözlendi. Prognozu belirlemede ilk saatlerdebakılmış olan transforming growth faktör beta ve platelet aktiveting faktörasetilhidrolaz düzeylerinin anlamlı olmadığı kanısına varıldı.Anahtar Kelimeler: Respiratuar distres sendromu tip 1, respiratuar distressendromu tip 2, mekonyum aspirasyonu sendromu, endotelin-1, transforming growthfaktör beta, platelet aktiveting faktör asetilhidrolaz, yenidoğan.2

THE LEVELS OF PLASMA ENDOTHELIN -1, PLATELETACTIVATING FACTOR ACETYL HYDROLASE, TRANSFORMINGGROWTH FACTOR BETA-1 AND SERVICEABLE OF THESE MARKERSAT DIFFERENTIAL DIAGNOSIS IN NEWBORN INFANTS DIAGNOSISWITH RESPIRATORY DISTRESSThe most important reasons for the extension of hospital period in prematurebirths, are the problems that are related to respiratory system. Respiratory distresssyndrome type 1, respiratory distress syndrome type 2, meconium aspirationsyndrome are the most common reasons of respiratory distress, while early diagnoseof the disease and appropriate treatment started on time, are also important forincreasing the life quality and extending the lifetime period.The increased levels of endothelin-1, which is responsible forbronchoconstruction and vasoconstruction in many organ insufficiencies are relatedto the bed prognose. Despite the fact that transforming growth factor beta has anrectifier impact on inflamation and increaser impact on tissue recovery; its extremeaccumulation leads to the extension of inflamation and fibriosis. Another cytokineplatelet activating factor, causes vasoactive impact on the lungs and inducesbronchoconstruction. Platelet activating factor acetylhydrolases, is the enzyme,which counteracts PAF by decomposing it.In this study, the assessment of signifance for the consideration of serumendothelin-1, transforming growth factor beta-1 and platelet activating factoracetylhydrolases levels in the distinctive diagnose, follow-up of the newborns withrespiratory distress and determination of prognose, are aimed.3The babies, who were taken to newborn intensive care unit, have beenincluded within the scope of this study. A study group of 100 newborns; 62 of whichwith RDS type 1 diagnose, 24 of which had RDS type 2 diagnose, and 14 of whichhad meconium aspiration diagnose within one year, has been established. Also, acontrol group of 20 premature and mature babies without any problem has beenestablished. It has been found out that endothelin-1, transforming growth factor betaand platelet activating factor acetylhydrolase did not differentiate in the controlgroup of premature and mature babies; but endothelin-1 and transforming growthfactor beta was increased in RDS type 1 and RDS type 2, while they were increasedmost in meconium aspiration. The increase in the level of platelet activating factoracetylhidrolases has been determined in only meconium aspiration. It has beenobserved that, endothelin-1 checks at the early hours were rather useful for thedetermination of prognose and endotelin-1 checks during the further days were ratherexpressive for the indication of the recovery. It has been concluded that the levels oftransforming growth factor beta and platelet activating factor acetylhydrolases,which have been checked at early hours, were not expressive for the determination ofprognose.Key Words: Respiratory distress syndrome type 1, respiratory distresssyndrome type 2, meconium aspiration syndrome endothelin-1, transforming growthfaktör beta, platelet activating factor acetylhydrolases, newborn.4
The levels of plasma endothelin-1, platelet activating factor acetyl hydrolase, transforming growth factor beta-1 and serviceable of these markers at differential diagnosis in newborn infants diagnosis with respiratory distress
Keywords: Çocuk Sağlığı ve Hastalıkları